Discussion of Teaching With Multiple Intelligences to Corporate Employees' Learning Achievement and Learning Motivation - Lei, Di-Yu; Cheng, Jui-Hsi; Chen, Chih-Ming; Huang, Kai-Ping; James Chou, Chiyang (Frontiers in Psychology, 2021)
The development of multiple intelligences used to focus on kindergartens and elementary schools as educational experts and officials considered that the development of students’ multiple intelligences should be cultivated from childhood and slowly promoted to other levels. Nevertheless, the framework of multiple intelligences should not be simply promoted in kindergartens and elementary schools, but was also suitable in high schools, universities, and even graduate schools or in-service training.Taking employees in Southern Taiwan Science Park as the research subjects, total 314 employees in high-tech industry are preceded the 16-week (3 hours per week for total 48 hours) experimental teaching research. The research results show that 1.teaching with multiple intelligences would affect learning motivation, 2.teaching with multiple intelligences would affect learning achievement, and 3.learning motivation reveals remarkably positive effects on learning achievement. According to the results to proposed discussions, it is expected to help high-tech industry, when developing human resource potential, effectively well utilize people’s gifted uniqueness